Obtenção de culturas iniciadoras para produção de kefir de leite adicionadas ou não de linhagem probiótica - Karen Costa (2023)
Kefir is a fermented beverage produced by inoculating of kefir grains in substrates such as milk. These grains consist of a diverse microbiota of lactic and acetic acid bacteria and yeasts. Despite several studies demonstrating the health benefits of consuming kefir, its consumption in Brazil is still incipient, and production is mostly carried out in domestic environments with direct inoculation of grains in the substrate to be fermented. The resulting drink is not standardized and may present sensory and rheological characteristics that vary according to the cultivation and maintenance conditions of the grains. An alternative to overcome this problem is the use of starter cultures as inoculum. Therefore, the aim of this study was to optimize the process of obtaining starter cultures that can be used in milk kefir production. Freeze drying and spray drying were tested as methods for preserving lactic acid bacteria (Bac1, Bac2, Bac3) and yeast (Lev1), and two starter cultures containing the dehydrated cultures were proposed. Culture C1 was composed of the three lactic acid bacteria and yeast, and in C2, the Bac1 strain was replaced by the bacterial strain P1, a strain with known probiotic potential. The effect of the culture dehydration methods on the viability and growth pattern of these strains using cryoprotectants (freeze drying) or carriers (spray drying) was investigated. Freeze dryed samples with skim milk and sucrose cryoprotectant had better viability maintenance (counts above 9.0 log CFU/g for lactic acid bacteria and 8.0 log CFU/g for yeast) and a shorter lag phase after 180 days of refrigerated storage. The production of the beverages was standardized by using starter cultures C1 and C2, and fermentation was carried out for 13 hours until reaching the desired pH (4.6). In addition to these two drinks, a third one was prepared (C3) was prepared, in which the probiotic strain P1 was added. The C1 and C3 beverages exhibited a minimum concentration of total lactic acid bacteria and yeasts that characterize milk kefir, according to Normative Instruction No. 46 of 2007. Moreover, they presented similar physicochemical parameters (pH, centesimal composition, and organic compounds) to those obtained for the control (KLCU) and were more preferred by in the sensory evaluation (p < 0.05) in terms of texture, flavor, and overall impression attributes. According to the evaluators, in case of commercialization of these fermented milks, there was a higher intention to buy the beverages prepared with C1 and C3 cultures (p < 0.05). The daily ingestion of fermented beverages C1 and C3 by conventional mice challenged with Salmonella enterica subsp. enterica sor. Typhimurium did not result in statistically different survival rates compared to the control group (p > 0.05), only the group treated with KLCU showing higher survival (p = 0.0183). The lack of protection observed for C3 may be attributed to the low concentration of the strain with probiotic properties in the daily dose administered to the mice, which needs to be further investigated. Our results allow us to conclude that it was possible to develop an innovative starter culture composed of microorganisms isolated from circulating kefir grains in Brazil. This culture was able to produce a beverage within the identity standards determined by legislation, regarding microbiological and physicochemical properties, and well accepted by a panel of evaluators. It is also important to emphasize that the addition of the probiotic strain P1 did not affect any of the parameters evaluated for the beverage produced with the starter culture C1.